2023
DOI: 10.1038/s44318-023-00014-z
|View full text |Cite
|
Sign up to set email alerts
|

The IRE1β-mediated unfolded protein response is repressed by the chaperone AGR2 in mucin producing cells

Lisa Neidhardt,
Eva Cloots,
Natalie Friemel
et al.

Abstract: Effector mechanisms of the unfolded protein response (UPR) in the endoplasmic reticulum (ER) are well-characterised, but how ER proteostasis is sensed is less well understood. Here, we exploited the beta isoform of the UPR transducer IRE1, that is specific to mucin-producing cells in order to gauge the relative regulatory roles of activating ligands and repressing chaperones of the specialised ER of goblet cells. Replacement of the stress-sensing luminal domain of endogenous IRE1α in CHO cells (normally expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…This result could represent a decreased response to ER stress in mice without Fmo5. Considering how imperative it is for goblet cells to effectively complete the many steps involved in producing and secreting mucus, the ER of GCs has evolved to include an additional ER-UPR arm in AGR2/IRE-1β that is specifically sensitive to Muc2 31, 32 . We measured protein levels of the chaperone for this arm, AGR2, and find that AGR2 levels are significantly higher in Fmo5 -/- mice than wildtype ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could represent a decreased response to ER stress in mice without Fmo5. Considering how imperative it is for goblet cells to effectively complete the many steps involved in producing and secreting mucus, the ER of GCs has evolved to include an additional ER-UPR arm in AGR2/IRE-1β that is specifically sensitive to Muc2 31, 32 . We measured protein levels of the chaperone for this arm, AGR2, and find that AGR2 levels are significantly higher in Fmo5 -/- mice than wildtype ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the BiP/IRE-1α arm of the UPR senses a wide variety of ligands that cause ER stress but does not respond to excess Muc2 presence 31 . A mucin-sensitive UPR ER arm made up of AGR2 and IRE1β is hypothesized to take on the responsibility for the folding of mucins in goblet cells 31, 47 . A study by Grey et al .…”
Section: Discussionmentioning
confidence: 99%
“…XBP1s and XBP1u fragments were amplified from cDNA by PCR using primers flanking the splicing site identified by IRE1 with NEB Q5® High-Fidelity 2X Master Mix, as previously reported (Neidhardt et al, 2023). Briefly, XBP1u (255bp) and XBP1s (229bp) were separated in a 3 % agarose gel by electrophoresis and stained with SYBR Safe nucleic acid gel stain (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…XBP1s and XBP1u fragments were amplified from cDNA by PCR using primers flanking the splicing site identified by IRE1 with NEB Q5 High-Fidelity 2X Master Mix, as previously reported ( Neidhardt et al, 2024 ). Briefly, XBP1u (255 bp) and XBP1s (229 bp) were separated in a 3% agarose gel by electrophoresis and stained with SYBR Safe nucleic acid gel stain (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%